1962
DOI: 10.1104/pp.37.2.238
|View full text |Cite
|
Sign up to set email alerts
|

Riboflavin Nullification of Inhibitory Actions of 3-Amino-1,2,4-Triazole on Seedling Growth

Abstract: The phy.siological meclhanismls involved inl the toxic actions of 3-amino-1 ,2,4-triazole (aamitrole)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1964
1964
1995
1995

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Heretofore, the molecule has been consid ered relatively stable under most conditions but readily susceptible to microbial degradation. Amitrole is known to decompose in the presence of riboflavin and light (6,11,12,17) with the ultimate evolution of C0 2 5 originat ing from the amitrole molecule. The amitrole nucleus also is readily disrupted by high energy processes involv ing free radical systems (5,17).…”
Section: Resultsmentioning
confidence: 99%
“…Heretofore, the molecule has been consid ered relatively stable under most conditions but readily susceptible to microbial degradation. Amitrole is known to decompose in the presence of riboflavin and light (6,11,12,17) with the ultimate evolution of C0 2 5 originat ing from the amitrole molecule. The amitrole nucleus also is readily disrupted by high energy processes involv ing free radical systems (5,17).…”
Section: Resultsmentioning
confidence: 99%
“…If it turns out that there is only one cyclase enzyme, the observation that flavins are able to nullify the inhibitory' action of amitrole on the growth and chlorosis of barky seedlings (Hilton 1962) offers an opportunity for further investigation. Lycopeoe cyclase of Synechococcus, Envinia species, as well as phytoene desaturase from Synechococcus contain in the N-terminal amino acid sequences a flavin binding motif {Cunninghan et al i994).…”
Section: Discussionmentioning
confidence: 99%
“…T h e y postulated an alkylation of the pro tein by amitrole based on free radical formation when riboflavin and light were present. Hilton (7) found that riboflavin deactivated amitrole i n both light and dark, suggesting the possibility that light may not be necessary to produce amitrole-free radical. Possibly, endogenous energy systems initiate a free radical of amitrole that i n turn alkylates bean protein i n the dark.…”
Section: Discussionmentioning
confidence: 99%